Использование симметрии для построения решений уравнений Максвелла в среде - Цифра, И.М. (Доповіді НАН України, 2010)
Методом групової редукцiї отримано аналiтичний розв’язок рiвнянь Максвелла в середовищi. Знайдено класи неоднорiдних середовищ, для яких розв’язки рiвнянь Максвелла генеруються з розв’язкiв для однорiдного середовища. Отриманi результати можна використовувати для тестування числових методiв розв’язання тривимiрних задач геоелектрики в неоднорiдних середовищах. An analytic solution of the Maxwell equations in a medium has been obtained with the help of the group reduction method. A class of heterogeneous media, for which the solution of the Maxwell equations can be obtained from the solution for a homogeneous medium is found. The results obtained can be used for testing the numerical methods of solving the three-dimensional geoelectric problems in heterogeneous media.